Phytoplankton Drivers of Dissolved Organic Material Production in Colorado Reservoirs and the Formation of Disinfection By-Products - Khan, Alia L.; Sokol, Eric R.; McKnight, Diane M.; Saunders, James F.; Hohner, Amanda K.; Summers, R. Scott (Frontiers in Environmental Science, 2021)
Previous studies have shown that algal-derived dissolved organic matter (DOM) has a strong influence on the formation of disinfection byproducts (DBPs) during the treatment of drinking water. In the summer of 2010, we evaluated the role of nitrogen and phosphorus loading and phytoplankton abundance as drivers of the concentrations and quality of DOM and the associated DBP formation in 30 reservoirs in the mountains and plains of the State of Colorado. Optical properties such as Specific Ultraviolet Absorbance at 254 nm (SUVA254) and fluorescence spectroscopy were used to characterize DOM quality. Nutrient concentrations such as total nitrogen were also assessed and were associated with high concentrations of chlorophyll a (Chl-a). In turn, high total organic carbon (TOC) concentrations were associated with high concentrations of Chl-a, and the DOM in these reservoirs had a fluorescence signature indicative of contributions from phytoplankton growth. The reservoirs with TOC concentrations above 4 mgC/L were predominantly located in the plains and many are impacted by agricultural runoff and wastewater discharges, rather than in the mountains and are characterized by warm water conditions and shallow depths. For a subset of fourteen reservoirs, we characterized the composition of the phytoplankton using a rapid imaging microscopy technique and observed a dominance by filamentous Cyanobacteria in reservoirs with TOC concentrations above 4 mgC/L. The combination of high TOC concentrations with microbial characteristics resulted in high potential for production of two major classes of regulated DBPs, trihalomethanes and haloacetic acids. While fluorescence spectroscopy was useful in confirming the contribution of phytoplankton growth to high TOC concentrations, evaluation of predictive models for DBP yields found that all equally predictive models included SUVA254 and some of these models also included fluorescence indices or logTOC. These findings provide a limnological context in support of the recent guidelines that have been implemented for protection of high-quality drinking water supplies in the State of Colorado.